Implementation of the Project-Based Assignment Method for Making Eco Print Totebags to Improve Student Creativity in SBdP Learning - Diajeng Fatimatuz Zahro; Ita Aristia Saida (International Journal of Education and Learning, 2026)
Cultural Arts and Crafts (SBdP) learning in elementary schools plays an important role in developing students' creativity through meaningful practical activities. The reality in the field shows that the art learning process often still focuses on explaining theory, so students' opportunities to explore and develop creative ideas are not yet optimal. This study aims to describe the implementation of the project-based method of making eco print tote bags, the process of developing students' creativity, as well as the impact of applying this method on students' creativity in SBdP learning at MI Az-Zahro Panunggalan. This research uses a qualitative approach with a case study type of research. Data collection techniques were conducted through observation, interviews, and documentation involving teachers and students in SBdP learning activities. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. Research results indicate that the application of the project task method through eco-print tote bag making activities is able to create more active, collaborative, and creative learning. Students are directly involved in the process of exploring natural materials, designing motifs, as well as practicing the creation of artworks that promote the development of creative thinking skills. In addition, project activities also increase self-confidence, interest in learning, and the ability to collaborate among students in the learning process.